2008
DOI: 10.1039/b711341b
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic oxygen diffusion properties in epitaxial thin films of La2NiO4+δ

Abstract: We report on the development and validation of a new methodology for the determination of anisotropic tracer diffusion and surface exchange coefficients of high quality epitaxial thin films in the two perpendicular directions (transverse and longitudinal), by the isotopic exchange technique. Measurements were performed on c-axis oriented La 2 NiO 4+d films grown on SrTiO 3 (100) and NdGaO 3 (110) by pulsed injection metal organic chemical vapour deposition (PIMOCVD), with different thicknesses ranging from 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
198
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 184 publications
(226 citation statements)
references
References 22 publications
14
198
3
1
Order By: Relevance
“…6,12,13,[17][18][19][20][21][22][23] In support of our second hypothesis, lattice strain was recently shown to alter the oxygen defect chemistry as well as the oxygen reaction and diffusion kinetics on perovskite oxides.…”
Section: Introductionsupporting
confidence: 57%
“…6,12,13,[17][18][19][20][21][22][23] In support of our second hypothesis, lattice strain was recently shown to alter the oxygen defect chemistry as well as the oxygen reaction and diffusion kinetics on perovskite oxides.…”
Section: Introductionsupporting
confidence: 57%
“…6,10 For La 2 NiO 4 , previous experimental studies determined activation energies for oxygen diffusion in the range of 0.19 eV (for epitaxial thin films) to 0.90 eV (for single crystals). 10,15,17 Interestingly, a number of diffusion mechanisms were proposed for the oxygen transport in this material. 6,10,15 A summary of these results is given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Additionally, the first members of the RP series with n = 1, A 2 BO 4 , that exhibit the K 2 NiF 4 structure are also being considered for oxygen sensors and oxygen separation membranes. [5][6][7][8][9][10][11][12][13][14][15][16][17] These materials have been extensively investigated since the observation of high-temperature superconductivity in La 2Àx Ba x CuO 4 . 18 An interesting and recent example of a composite SOFC cathode has been the work of Sase et al, 19 which demonstrated higher transport and an oxygen exchange rate that was higher by three orders of magnitude at the interface of the perovskite (La,Sr)CoO 3 and the RP phase (La,Sr) 2 CoO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of strain was not clearly demonstrated or explained. On another material system, Burriel et al investigated epitaxially grown La 2 NiO 4 (c-axis perpendicular to the substrate surface) on SrTiO 3 (100) and NdGaO 3 (110) with thicknesses from 33 nm to 370 nm [57], with seemingly contradictory results to those shown on the strained LSC films. While the La 2 NiO 4 films grown on STO were compressively strained, those grown on NdGaO 3 were under tensile strain.…”
Section: Strain Segregation and Reactivitymentioning
confidence: 99%
“…These results provide insight into the strain and reactivity correlation of SOFC cathode materials. Isotope exchange depth profiling (IEDP) in combination with time of flight secondary ion mass spectroscopy (ToF-SIMS) has been used to determine the diffusion coefficients and oxygen surface exchange rates for several materials relevant to SOFCs [2,56,57]. Zapata et al used this method to determine the anisotropic diffusion coefficients and surface exchange rates of oxygen in thin films of the double perovskite GdBaCo 2 O 5+δ .…”
Section: Transport and Reactivitymentioning
confidence: 99%